Informativity of borehole geophysical methods in choosing the location of the main structures of the hydroelectric power plant (HPP) - S. Deyneko; S. Vyzhva; A. Bernevek (Геофизический журнал, 2017)
To study the state of the rock massif on the territory of the HPP on the river Vele (Republic of Equatorial Guinea) geophysical surveys using vertical seismic profiling, inter-well seismic survey and inter-well seismic tomography are performed. On the basis of the data obtained, there are significant differences in the state of crystalline rocks on the left-bank and right-bank sections of the dam construction. On the right-bank part of the territory, rock is more secure (about 90 % of the inter-wellbore space under study is characterized by a longitudinal wave propagation velocity (VP) of more than 4,500 m/s. On the left bank, for approximately 70 % of the investigated soil thickness VP is more than 4,500 m/s. The rock safety index allowed to obtain a rapid assessment of the state of the rocks in the massif, the rock was divided into four subzones: A — very strong unloading effect with the disintegration of rocks to eluvium, B — a strong manifestation of unloading and weathering, C — a weak manifestation of surface weathering and a moderate Manifestations of unloading, D — rocks are almost non-weathering, there are only signs of linear weathering in subvertical tectonic disturbances and large cracks. According to the results of the inter-well seismic tomography performed, it is also established that the more disrupted rocks are characteristic of the left-bank part of the construction site. Taking into account the obtained data, the plan for the location of the main structures of the dam of the hydroelectric power station is clarified.